Molecular dynamics simulations of singlet oxygen atoms reactions with water leading to hydrogen peroxide. (12th May 2020) - Xu, Shaofeng; Jirasek, Vit; Lukes, Petr
Abstract: The formation mechanisms of hydrogen peroxide due to the interaction of oxygen atom from the cold atmospheric plasmas in contact with water are not fully understood. Previous work on molecular dynamics (MD) simulations of interactions of O atoms in bulk water based on reactive force field and density-functional tight-binding method did not observe the formation of H 2 O 2 . In this work we applied density functional theory in MD simulations of 192 trajectories considering 63 H 2 O − O system to explore the reaction mechanisms for atomic oxygen radical in water. Our calculations revealed that triplet (ground) state oxygen was not reactive. Oxywater-similar structure O − O H 2 was a transient product. Perhydroxyl anion O − O H − and its counterpart hydronium H 3 O + were formed. In most of simulated cases, hydrogen peroxide was observed as a final product. The formation pathways of hydrogen peroxide exhibited large complexities for the simple hydrogen bonded system. According to the sources and pathways of the hydrogen atom being bonded in hydrogen peroxide molecule, mechanisms can be classified into (1) hydrogen-abstraction, (2) hydrogen-transfer n (n = 3, 4, 5, 6, 7, 8), (3) proton-delivery n = 2, 3, (4) proton-transfer. It was confirmed that for correct prediction of reaction mechanisms is better to use quantum molecular dynamic simulations.